Organic chemistry - Patrick, Graham L. (Instant notes series. Chemistry series., 2004)
Instant Notes in Organic Chemistry, 2/e concentrates entirely on the basics of the subject without going into exhaustive detail or repetitive examples. This is a student-friendly textbook and will help students understand the subject and.